2023
DOI: 10.1002/ab.22111
|View full text |Cite
|
Sign up to set email alerts
|

Childhood bullying victimization, emotion regulation, rumination, distress tolerance, and depressive symptoms: A cross‐national examination among young adults in seven countries

Madelyn H. Labella,
Neelamberi D. Klein,
Georgina Yeboah
et al.

Abstract: Existing research suggests a robust association between childhood bullying victimization and depressive symptoms in adulthood, but less is known about potential mediators of this link. Furthermore, there is limited cross‐national research evaluating similarities and differences in bullying victimization and its associations with mental health. The current study addressed gaps in the literature by evaluating cognitive and affective responses to stress (i.e., emotion regulation, rumination, and distress toleranc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Despite these weaknesses, this study suggests that interventions focused on targeting dysfunctional cognitive processes to regulate the emotions of peer-victimized adolescents may alleviate the psychological maladjustment associated with this stressful experience [47]. For example, emotion coaching can be effective in helping adolescents to self-regulate their emotions at school, promoting emotional competencies and positive peer interactions [96,97].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Despite these weaknesses, this study suggests that interventions focused on targeting dysfunctional cognitive processes to regulate the emotions of peer-victimized adolescents may alleviate the psychological maladjustment associated with this stressful experience [47]. For example, emotion coaching can be effective in helping adolescents to self-regulate their emotions at school, promoting emotional competencies and positive peer interactions [96,97].…”
Section: Discussionmentioning
confidence: 94%
“…However, they did not assess the effect on other psychopathological symptoms. In contrast, Labella et al [47] found that specific emotion regulation strategies mediated the association of bullying victimization with depression. However, the authors did not evaluate cognitive strategies and used a sample of young adults.…”
Section: Introductionmentioning
confidence: 87%